Sosialisasi dan Pendampingan Internet Sehat dan Aman Untuk Remaja - Eki Aryadi; Muasir Pagan (Pusat Riset dan Inovasi Nasional, 2024)
The internet has flaws that hurt humanity. This is more due to the way information is presented on the Internet which is too free. This allows kids to see and read all kinds of things they don't have time to see and read. On the one hand, the Internet can be a threat to the younger generation, on the other hand, the Internet is also a new way to expand knowledge and increase individual potential and abilities as successors of the country. Community Service Activities (PKM) Socialization and Assistance for Healthy and Safe Internet for Teenagers at the Nurul Hasanah Health Vocational School was held on 5-10 February 2024 with a total of 30 participants. Socialization was provided by the community service team regarding the definition of the internet, internet functions, positive and negative aspects of the internet, understanding Healthy and Safe Internet (INSAN), and so on. The extension participants seemed enthusiastic about the materials presented by the resource persons and were able to be actively involved, so this extension activity took place in a two-way system and many participants asked questions. The presentation of the extension material was followed by discussion, ice-breaking, and distribution of door prizes to participants who were active during the discussion activities.